The impact of liabilities management on achieving bank profitability: Applied research in a sample of Iraqi private commercial banks (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The aim of the research is to show the impact of liabilities management in achieving the bank's profitability for the period from (2011-2020). The research sample included banks (Baghdad, Gulf, Credit). In order to achieve the goals and reach the results, the research relied on the inductive approach and the analytical descriptive approach, depending on the Excel 2020 program. The research found a relationship between liability management and banking profitability. The research reached the most important conclusions, namely, that the commercial banks, the research sample, were of varying profitability during the years of research among them, and this is evidence that the banks were not able to properly manage their liabilities. The research also recommended the necessity of involving the banking cadre in specialized and technical courses and workshops to ensure their knowledge of liabilities management and how it affects the achievement of banking profit.